Réponses

2014-04-13T14:20:36+02:00
B = (6x-7) (3-2x)
    = 6x X 3 - 6x X 2x - 7 X 3 - 7 X 2x
    = 18x - 12x (au carré) - 21 - 14x
     = 4x - 12x (au carré= - 21

 Pour x = 0

( 6 X 0 - 7 ) ( 3-2 X 0)
=( 0- 7) (3-0)
= 7 X 3
= 21

Pour x = 1

( 6 X 1 - 7) ( 3 - 2 X 1)
= (6-7) ( 3- 2)
= -1 X 1
= - 1                 Voilà :)
Meilleure réponse !
2014-04-13T14:22:22+02:00
Salut :)

1) Développer et réduire l'expression :               
B = (6x-7) (3-2x)  
B = 18x - 12x² - 21 + 14x
B = -12x² + 32x - 21

2) Tester la réponse pour x = O, puis pour x = 1.


Pour x = O :
B = (6x-7) (3-2x)
B = -12x² + 32x - 21
B =  -12 x 0²² + 32 x 0 - 21
B = -21

Pour x = 1 :
B = (6x-7) (3-2x)  
B = (6 x 1 - 7)(3 - 2 x 1)
B = (6 - 7)(3 - 2)
B = -1 x 1
B = -1

J'espère t'avoir aidé(e) ! :)